Mnogostoritvena omrežja, integracija podatkov, govora in videa - Gruškovnjak, Jože (Uporabna informatika (Ljubljana), 1999)
Multiservice networking is emerging as a strategically important issue for enterprise and public service provider infrastructures alike. The proposition of multiservice networking is the combination of all types of communications -data, voice, video - 0ver a single packet or cell-based infrastructure. The benefits of multiservice networking are reduced operational costs, higher performance, greater flexibility, integration and control, and faster new application and service deployment.
Keywords: govor (telekomunikacije); integracija; komunikacije; video